6=3s-s

Simple and best practice solution for 6=3s-s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=3s-s equation:



6=3s-s
We move all terms to the left:
6-(3s-s)=0
We add all the numbers together, and all the variables
-(+2s)+6=0
We get rid of parentheses
-2s+6=0
We move all terms containing s to the left, all other terms to the right
-2s=-6
s=-6/-2
s=+3

See similar equations:

| (t+4)^2-13(t+4)+42=0. | | -12=-5c+2c | | -35=-5t-2t | | 3x=4,86 | | 10x=8=98 | | 8=I-5i | | -15=-2j-j | | -7=2u+5u | | 8x(5+7)=40+ | | |y|+6=21 | | 15+2x=3x-15=15 | | 6.2x÷1.2=8.9 | | 4(2y+2)-3(3y+2)=-2 | | 4x−14=26 | | 13x-5=12x+16 | | 2/9b+1/3b=4/9-1/3b | | 6(6y-2)-7(5y+5)=4 | | 2700=700+900x-100x^2 | | 36y-12-35y+35=4 | | (3t-4)^2+46t=31 | | 2x+5=5+2 | | x2+x+1=x+1 | | -96=-8y | | x2+2x=x+6 | | 55x−7=3x+15 | | 5x−7=3x+15 | | 4(x+1)=72 | | 1.13^x=100 | | 6-4(3-2x)=5x-9 | | 8x+42=x | | -22=3(y-6)-5y | | 2-0.4+12=r |

Equations solver categories